Cladistic analysis of Zethus Fabricius, 1804 (Hymenoptera, Vespidae): a new subgeneric classification - Lopes, Rogerio Botion [UNESP]; Carpenter, James M.; Noll, Fernando Barbosa [UNESP] (Pensoft Publishers, 2021)
Zethus is the largest genus in Vespidae with over 270 species. It is currently divided into four subgenera: Z. (Zethus), Z. (Zethoides), Z. (Zethusculus) and Z. (Madecazethus). While the last three are restricted to certain biogeographic areas, the first is spread through western and eastern hemispheres. Studies have shown possible phylogenetic incongruence regarding this current division and even raised the possibility of paraphyly in the genus. To evaluate this classification, morphological pasimony analyses under implied weights was carried out, examining external morphology and male genitalia. Analyses showed paraphyly of the genus under various k values and paraphyly of two subgenera. Ischnocoelia and Ctenochilus are lowered to subgenera of Zethus. Zethus (Madecazethus) is no longer restricted to Malagasy species and now includes those of the African continent as well. Zethus (Zethastrum) subg. nov. is defined for Oriental representatives. Z. (Zethus) is subdivided into three subgenera: Z. (Zethus), Z. (Didymogastra) and Z. (WettsteinM). Zethus (Zethusculus) and Z. (Zethoides) are monophyletic and hold their status as subgenera. Three species-groups are Incertae sedis: Z. albopictus, Z. pallidus and Z. spinosus.
Keywords: Phylogeny; taxonomy; paraphyly; sensitivity analysis; Zethini